High-throughput siRNA Screen Identifies MTX2 as a Novel Mediator of Mitochondrial Morphology - Gaetz, Matthew (Université d'Ottawa / University of Ottawa, 2014)
Mitochondria exist in a dynamic network whereby fusion and fission events are critical to the health of the mitochondria, the cell, and the organism. Dysfunctional mitochondrial dynamics underlie a plethora of diseases including various cancers, heart diseases, diabetes, neurodegenerative diseases, and a number of mitochondrial disorders. Despite a strong molecular knowledge of a handful of functional mediators of mitochondrial dynamics, much less is known about how this process is regulated at a cellular level, and what genes are involved in signaling pathways. A previously completed mitochondrial morphology genome screen was repeated with an automated confocal microscope resulting in the identification and validation of MTX2 as a novel regulator of mitochondrial dynamics. Functional characterization of the role of MTX2 in mitochondrial dynamics will further our understanding of mitochondrial biology, and has the future potential to inform therapies for some of the many diseases underscored by dysfunctional mitochondrial dynamics.
Keywords: Mitochondria; MTX2; High-throughput screening; RNAi